229k views
2 votes
Rearrange your equation from part A by setting it equal to 0 and substituting y for 0. Then write the equation in the form y = (x – h)2 – c.

User Axelrod
by
7.0k points

2 Answers

4 votes

Answer:

y = (x - 1)^2 - 8

Explanation:

Your answer from part A should be: (x - 1)^2 = 8

You are simply changing the format of the equation from

0 = (x - 1)^2 - 8 to y = (x - 1)^2 - 8

Hope this helps!

User TheMukhiddin
by
6.0k points
3 votes

Answer:

y = (x-1)² - 8

Explanation:

The response from part A is (x – 1)2 = 8, where h = 1 and c = 8.

Set the equation equal to 0:

0 = (x – 1)2 – 8.

Substitute y for 0 and keep the equation rewritten in the form y = (x – h)2 – c:

y = (x – 1)2 – 8.

User Vancexu
by
5.9k points